A theory of negative lyricism. Issue 10 (2nd October 2020) - Dunk, Jonathan
ABSTRACT: This paper examines the philosophic and political potentials of lyric poetry through an archaeology of its ideological participation, situating a critical moment of the form's partial liberation in the poetry of Paul Celan.